Teknik Counter Pressure Mengurangi Intensitas Nyeri Persalinan Kala I Fase Aktif - Huda, Samsil; Syahriani, Syahriani; Syamson, Meriem Meisyaroh; Hamdiyah, Hamdiyah; Hasriani, St. (Jurnal Kebidanan Malakbi, 2024)
Lower back pain is a frequent symptom during pregnancy, often worsening as the pregnancy progresses. The shifting center of gravity, hormonal changes, and increased weight gain associated with pregnancy can contribute to lower back pain and discomfort. While pharmacological interventions are sometimes necessary, there is growing interest in non-pharmacological approaches that may provide relief without potential side effects. Counter pressure is a type of massage that uses your fists to apply constant pressure to the patient's spine during compression. Anti-stress information can also be applied to the lower back in a straight or circular motion. Back compression techniques can relieve back pain during labor contractions. Objective to determine the level of labor pain in the first stage of the active phase of labor in women giving birth at the Rappang Health Center in Sidrap Regency before back massage is carried out with the counter pressure technique. To find out labor pain in the first stage of the active phase of labor in women giving birth at the Rappang Health Center, Sidrap Regency, after doing back massage using a counter pressure technique. The type of research used is pseudo- or quasy-experimental research with a Two-Group Posttest Only design. The relaxation technique obtained a mean rank of 18.25, while the group that underwent counter pressure obtained a value of 6.75. So the average pain in the group that only got the relaxation technique was higher than that done with masse counter pressure with a p value (0.000) <0.05 so it can be concluded that counter pressure massage is effective in reducing pain intensity in laboring mothers. There is an influence of the Counter Pressure massage technique to reduce the intensity of labor pain during the first active phase at the Rappang Health Center, Sidrap Regency. Counter pressure could potentially be a useful technique for managing labor pain.